(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
As digital credentials and verifiable records become central to systems of education, employment, identity, and access, the urgency to mitigate the harm they may cause is growing. While these technologies often promise empowerment, inclusion, and access to opportunities, they can also reproduce the very inequities they claim to resolve, particularly for marginalized, racialized, and justice-impacted communities. This session offered a care-centered and participatory space to pause, reflect, and strategize together. Led by Dr. Kelly Page, author of When Credentials Cause Harm, the session provided a facilitated caring environment where participants engaged in mutual learning, storytelling, and collaborative ideation around one guiding question: "How might we mitigate harm in the systems we build, use, and influence?" The session began with a grounding practice with Principles of Care (Figure 1) and an invitation to care and share stories of perceived risk and harm. This opening moment was an intentional shift away from typica rhetorical technology or techno-optimism discourse and into a space that centers people, emotions, and lived experiences of risk, harm, and mitigation. Figure 1. Principles of Care